Β-Blockers, Pneumonia, and Outcome After Ischemic Stroke. Issue 5 (May 2015) - Sykora, Marek; Siarnik, Pavel; Diedler, Jennifer; Lees, K.R.; Alexandrov, A.; Bath, P.M.; Bluhmki, E.; Bornstein, N.; Claesson, L.; Davis, S.M.; Donnan, G.; Diener, H. C.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Increased sympathetic drive after stroke is involved in the pathophysiology of several complications including poststroke immunudepression. β-Blocker (BB) therapy has been suggested to have neuroprotective properties and to decrease infectious complications after stroke. We aimed to examine the effects of random pre- and on-stroke BB exposure on mortality, functional outcome, and occurrence of pneumonia after ischemic stroke. Methods— Data including standard demographic and clinical variables as well as prestroke and on-stroke antihypertensive medication, incidence of pneumonia, functional outcome defined using modified Rankin Scale and mortality at 3 months were extracted from the Virtual International Stroke Trials Archive. For statistical analysis multivariable Poisson regression was used. Results— In total, 5212 patients were analyzed. A total of 1155 (22.2%) patients were treated with BB before stroke onset and 244 (4.7%) patients were newly started with BB in the acute phase of stroke. Mortality was 17.5%, favorable outcome (defined as modified Rankin Scale, 0–2) occurred in 58.2% and pneumonia in 8.2% of patients. Prestroke BB showed no association with mortality. On-stroke BB was associated with reduced mortality (adjusted risk ratio, 0.63; 95% confidence interval, 0.42–0.96). Neither prestroke BB nor on-stroke BB showed an association with functional outcome. Both prestroke and on-stroke BB were associated with reduced frequency of pneumonia (adjusted risk ratio, 0.77; 95% confidence interval, 0.6–0.98 and risk ratio, 0.49; 95% confidence interval, 0.25–0.95). Conclusions— In this large nonrandomized comparison, on-stroke BB was associated with reduced mortality. Prestroke and on-stroke BB were inversely associated with incidence of nosocomial pneumonia. Randomized trials investigating the potential of β-blockade in acute stroke may be warranted.